BUDAYA LOKAL DALAM MEMBANGUN KETAHANAN EKONOMI MASYARAKAT DESA BONE LOLIBU KECAMATAN BONE KABUPATEN MUNA - Hariani Hariani; La Janu (KABANTI : Jurnal Kerabat Antropologi, 2023)
This study aims to explain the function of local culture in building the economic resilience of the people of Bone Lolibu Village, Bone District, Muna Regency. The research method used is a qualitative method. The results of this research. The development of social life in building the economic resilience of the people of Bone Lolibu Village has progressed along with the development of science and technology, so little by little, there has been a change in the form of the grass cleaning tools used. Local culture is all forms of wisdom based on good values ​​that are believed, applied, and maintained for quite a long time (from generation to generation) by a group of people from the Bone Libu Village community. The culture of gotong royong has become a tradition for the people of Bone Lolibu, every time they have community events they help one another without being called on by them to come voluntarily. In increasing the economic resilience of the people of Bone Lolibu Village, clearing land for farming such as corn, beans, cassava, and sweet potatoes which are still planted traditionally because the people do not have the knowledge or education so they do according to what is known so far.